BIOMASS AND CARBON ABSORPTION IN MANGROVE LEAVES AND ROOTS IN LANTEBUNG ECOTOURISM, MAKASSAR CITY - Mesalina Tri Hidayani; Stanislaus William Permadhi; Sri Wulandari (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
This study aims to analyze biomass and carbon absorption in mangrove leaves and roots, especially Rhizophora mucronata and Avicennia alba. Data collection was carried out using purposive sampling techniques at two different location points. The measurement of biomass, carbon absorption in mangrove leaves and roots begins by taking samples using scissors and saws on the three predetermined trees and then taking them to the laboratory for analysis. The results showed that the average value of biomass in Avicennia alba leaves was higher (42.69 grams) than that of Rhizophora mucronata leaves (34.66 grams). Meanwhile, the highest average value of root biomass was in the mangrove Rhizophora mucronata (127.86 grams) compared to the root biomass of Avicennia alba (89.43 grams). The highest average value of leaf organ carbon absorption was in the mangrove Rhizophora mucronata (11.21%) compared to the mangrove Avicennia alba (9.09%). Meanwhile, the highest average value of root carbon absorption was in the Avicennia alba mangrove (12.17%) compared to the root carbon absorption of Rhizophora mucronata (10.85%). The results of the T-test showed that the carbon uptake in Rhizophora mucronata leaves differed significantly at 0.031 (<0.05) which means that Rhizophora mucronata leaves absorbed more carbon than Avicennia alba leaves, while others did not differ significantly (>0.05). The measured water quality parameters including temperature, pH, and salinity show that all water quality parameters are within the range of quality standards according to PP RI no. 21 of 2022 for marine life, except for the temperature at station 1 of the Rhizophora mucronata mangrove (Station 1: temperature 25.66 °C; pH 7.12; salinity 27.33 ppt and station 2: temperature 29.4 °C; pH 7.25; salinity 25.16 ppt.